PENGARUH PENGALAMAN MAGANG, MINAT KERJA, SOFT SKILL, DAN MOTIVASI KERJA TERHADAP KESIAPAN KERJA MAHASISWA TEKNIK INFORMATIKA UNIVERSITAS KRISTEN INDONESIA TORAJA - Melinda Allo; Rati Pundissing; Althon K. Pongtuluran (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to examine the influence of internship experience, work interest, soft skills, and work motivation on the job readiness of students in the Department of Informatics Engineering, Faculty of Engineering, Toraja Christian University of Indonesia, both partially and simultaneously. A quantitative approach was employed using primary data collected through questionnaires distributed to 2023 cohort students who had completed their internship program. The study involved 50 respondents selected using the Slovin formula and purposive sampling technique. Data were analyzed using multiple linear regression with IBM SPSS version 26, preceded by validity, reliability, and classical assumption tests. The results indicate that internship experience, work interest, soft skills, and work motivation each have a positive and significant effect on students' job readiness, with significance values below 0.05. Simultaneously, the four variables also have a positive and significant effect on job readiness, as indicated by an F-value of 25.750 and a significance level of 0.000. The coefficient of determination of 69.6% indicates that students' job readiness is explained by internship experience, work interest, soft skills, and work motivation, while the remaining 30.4% is influenced by other factors outside the research model. These findings highlight the importance of strengthening internship programs and developing both technical and non-technical competencies to enhance graduates' readiness for the increasingly competitive labor market.